Regional Economic Outlook, October 2010, Western Hemisphere : Heating Up in the South, Cooler in the North. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2010)
Heating Up in the South, Cooler in the North broadly describes the economic scene for the Western Hemisphere. The report emphasizes how a mixed environment--with slow recovery in the United States and other advanced economies, but strength in Asia--differently shapes the outlooks for the diverse economies of Latin America and the Caribbean. This issue also focuses on financial issues in Latin America, with a chapter on the challenges of allowing credit to expand safely, without creating excessive risks, and a chapter that looks at macroprudential financial policies--topics especially important in today's context of low global interest rates and capital flows to emerging economies. The final chapter turns to Caribbean economies, exploring the drivers, and obstacles, that affect their growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet